The Role of the Strategic Leader in Managing Small and Medium Enterprises at Sidi Bel Abbés Town, Algeria - Faiza, Sehimi; Abdelmadjid, Ezzine (The Arab Journal of Administration, 2020)
This study is designed to explain the role of strategic leader in managing his Enterprises by studying the relationship between transformational leadership and the strategic performance in small and medium industrial Enterprises. The sample size of the study was 20 research sample in the town of Sidi Bel Abbés, and it is a small intentional sample. The concept of transformational leadership was measured through five dimensions: idealized influence, inspirational motivation, intellectual stimulation, individual consideration and empowerment, and measuring strategic performance across four dimensions: finance, clients, internal processes, learning and growth. We have tested two hypotheses, the first was: there is a statistically significant relationship between transformational leadership with its five dimensions and strategic performance, and the second is the presence of variable organizational change which is the mediating variable in the relationship between transformational leadership and strategic performance. The study concluded that there is a statistically significant relation between all dimensions of transformational leadership and strategic performance and it is positive. The high relationship was between empowerment and strategic performance is followed by the relationship between intellectual stimulation, individual consideration, inspirational motivation, idealized influence and strategic performance respectively; finally the empirical study did not confirm the impact of mediating variable. It emphasized the relationship between transformational leadership and organizational change and did not ascertain the relationship between organizational change and strategic performance.